Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I want to express $$\prod_{k=1}^n \left( k - \frac{1}{2} \right)$$ using the gamma function. I think this is equivalent to $\left(k-\frac{1}{2}\right)!$ so I set $a=k-1$ and then used the identity $$\Gamma \left(n+\frac{1}{2}\right) = {(2n)! \over 4^n n!} \sqrt{\pi}$$ to get $$\prod_{k=1}^n \left( k - \frac{1}{2} \right) = \left(a+\frac{1}{2}\right)! = {\Gamma(2k - 1) \over 4^{k-1} \Gamma(k)} \sqrt{\pi}$$ However, Wolfram Alpha disagrees with this much more succinct answer: $$\frac{\Gamma\left(k+\frac{1}{2}\right)}{\sqrt{\pi}}$$

Wolfram Alpha's answer looks more like the integer relation between gamma and factorial... except for the factor of $\sqrt{\pi}$ that I'm at a loss to explain. How do I get from my finite product to this expression?

share|improve this question
${\large\Gamma\left(n + 1/2\right)/\sqrt{\,\pi\,}\,}$. –  Felix Marin Mar 20 at 22:03

3 Answers 3

up vote 4 down vote accepted

Define $a_n:=\prod_{k=1}^n\left(k-\frac 12\right)$. From the relationship $\Gamma(x+1)=x\Gamma(x)$ for $x$ positive, we derive $$k-\frac 12=\frac{\Gamma(k+1-1/2)}{\Gamma(k-1/2)},$$ hence the product which defines $a_n$ is telescopic. We obtain $$a_n=\frac{\Gamma(n-1/2)}{\Gamma(1/2)}.$$ Since $\Gamma(1/2)=\sqrt\pi$, we get the same formula as Wolfram Alpha.

share|improve this answer
Ugh, I was so overwhelmed by the other answers that I missed yours which is succinct and to the point (and essentially what I wrote). Another deletion for me. (+1) –  robjohn Mar 20 at 22:37

The first type of identity needs no gamma function at all to arrive at a correct result. $$ \prod_{k=1}^n\left(k-\tfrac12\right)=\frac1{2^n}\prod_{k=1}^n(2k-1) =\frac1{4^nn!}\prod_{k=1}^n(2k)(2k-1)=\frac{(2n)!}{4^nn!} $$

share|improve this answer

The factorial has two equivalent definitions. First, the one I expect you have learnt

$k!=k\cdot(k-1)\ldots2\cdot1$ or, "$k$ factorial is the product of all the integers from $1$ up to $k$"

This is a good definition in that it's natural - it seems sensible given the situations in which the factorial is helpful (in combinatorics, for instance). On the other hand, it does not lend itself to sensible generalisations. There is an equivalent definition, though, in the form of a recurrence relation.

$k!=k\cdot (k-1)!$ , and $1!=1$

Now, this is obviously the same as the first definition when $k$ is a positive integer, but if we define a sensible value for, say, $(1/2)!$, then we can generate values of $(3/2)!$, $(5/2)!$, etc.

What you have done is set $(1/2)!=1/2$ (and, I would guess, $x!=x$ for all $x \in (0,1)$) and that's fine, but it turns out that, while this seems like a sensible generalisation, it isn't in fact the most interesting or natural one. Let's call your generalisation $f(x)$, and define it on the positive reals as $$f(x) = xf(x-1) \text{ and }f(x)=x \text{ if } x \in (0,1]$$ We have that $f(x)=x!$ when $x$ is a positive integer, and we can now put in any positive real we like. It disagrees with our usual convention of $0!=1$ when $x$ is near $0$, but that's fine too - we don't necessarily have to agree with that convention.

The Gamma function, though, is a little different. $\Gamma(x)$ is defined usually as $$\Gamma(x)=\int_{0}^{\infty}u^{x-1}e^{-u}du$$ and it can indeed be shown that $\Gamma(x+1)=x\Gamma(x)$ and $\Gamma(1)=1$, and therefore that $\Gamma(x+1)=x!$ when $x$ is a positive integer (which is a slight translation of our second definition for the factorial). However, $\Gamma(x)$ has a completely different set of values in $[0,1]$ than our $f(x)$ (including, strangely, that $\Gamma(1/2)=\sqrt{\pi}$). The reason this is usually the definition is that it comes up pretty much everywhere.

So the reason your two answers look similar is because any function satisfying the recurrence relation above will have a value at $n+1/2$ of that sort of form, but the specific value at $1/2$ is what introduced the $\sqrt{\pi}$.

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.